Theological Milton : deity, discourse and heresy in the Miltonic canon - Lieb, Michael, 1940- (Pittsburgh, Pa. : Duquesne University Press, 2006)
"Literature and theology are inextricably intertwined in this study of the figure of God as a literary character in the writings of John Milton"--Provided by publisher.
I. The discourse of theology. 1. Doctrinal and discursive contexts. 2. The ontological imperative. 3. The signatures of deity -- II. The poetics of deity. 4. The theopathetic deity. 5. The odium dei. 6. "Our living dread" -- III. The heresies of godhead. 7. The socinian imperative. 8. Arianism and godhead.
Includes bibliographical references (p. 279-338) and index.
Keywords: Milton, John, -- 1608-1674 -- Religion; Christianity and literature -- England -- History -- 17th century; Christian literature, English -- History and criticism; Christian heresies -- History -- Modern period, 1500-; Christian heresies in literature; Theology in literature; Heresy in literature; God in literature; Milton, John, -- 1608-1674 -- Religion